Psychological contract breach mediates ethical climate and deviance among nurses - Verma, Govind Gopi (Nursing ethics, 2025)
BackgroundHealthcare organizations are driven by mission-driven values, yet these values can be compromised in employee-organization relationships. Hospitals present psychologically challenging environments for their nurses, potentially causing breaches of psychological contracts. Despite extensive research on ethical climates, their impact on mitigating interpersonal deviance in healthcare remains understudied. This warrants investigation into how ethical workplace climates and breaches of psychological contracts affect interpersonal deviance in nurses.Research Objective/Purpose/AimThis study investigates how psychological contract breaches mediate the relationship between ethical climates and interpersonal deviance.Research Design/MethodThe study employs a cross-sectional design, collecting data from 230 nurses across five hospitals in India. Standard scales are used to measure the constructs in the study, with established reliability and validity. Structural equation modeling (SEM) was utilized to examine the hypotheses outlined in the study. We also tested the moderating effect of work experience in the moderated mediation model.Ethical considerationsThis study received ethical approval (#ERB-ASBC-2024-027) from the University Ethical Review Board, constituted at Amrita School of Business, Coimbatore.Participants and proceduresPermission to conduct the study was obtained from the hospital administration. Nursing staff participated voluntarily. They were informed about the survey’s purpose and their right to withdraw at any time. Consent was obtained on the survey form before recording their responses, and no personal identifiers were collected.FindingsAn ethical workplace climate reduces nurses’ interpersonal deviance, mediated by psychological contract breach. This mediation is moderated by work experience, with a stronger effect on less-experienced nurses.ConclusionThe study suggests that regular assessments of ethical workplace climate can aid in planning effective reinforcements at individual, leadership, or organizational level to reduce interpersonal deviance and perceptions of psychological contract breach.